70.3k views
2 votes
Given f(x)=3x²−6x−1.

What is the value of f(−2/3)

User Jsstuball
by
5.9k points

2 Answers

4 votes
f(-2/3) = 3(-2/3)^2 - 6(-2/3) - 1

= 3(4/9) - 6(-2/3) - 1
= 12/9 + 12/3 -1
= 4/3 + 12/3 - 3/3
= 16/3 - 3/3
= 13/3
= 4 1/3

User JackTheKnife
by
4.9k points
3 votes

Answer:

substitute x = -23 into equation

Explanation:

f(x) = 3x2-6x-1

this i interpret as 3 multiplied by 2. So,

f(x) = 6 -6(x) -1

substituting x = -23 ito f(x) , we get

f(-23) = 6 - 6 (-23) -1

f(-23) = 6 + 138 -1

f(-23) = 6 + 137

f(-23) = 143

User Vilalabinot
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.